Penggunaan Kalimat Efektif dalam Tugas Karya Ilmiah Mahasiswa D-3 Politeknik Baja Tegal - Ria Candra Dewi; Kusumaningroem, Ismi (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2021)
This study aims to analyze the use of effective sentences in scientific essay assignments in general subjects D-3 programme at Baja Tegal Polytechnic regarding the use of effective sentences. Research method uses in this research is qualitative. Based on the analysis in the research essay of D3 programme Polytechnic Baja Tegal Semester III, several errors were found in writing sentences. These mistakes result in ineffectiveness in the sentence so that the reader finds it difficult to understand the writing. The manifestation of the error is the use of excessive words that make the ineffective sentence. Also, choosing words that are not right for sentences such as conjunctions and prepositions that make ineffective sentence.